Perancangan Desain Antarmuka Website Sekolah Menengah Atas Menggunakan Metode Goals Directed Design - Aldito Doni Pasha; Ayouvi Poerna Wardhanie; Endra Rahmawati (Maranatha University Press, 2023)
SMA Muhammadiyah 9 Surabaya is a school located in the city of Surabaya. The school uses the website as a medium for introducing school information, but when using the website, a problem is found, such as a lack of usability, convenience and user satisfaction. In the situation of the corona virus pandemic, educational services have become a service that must be provided to students or the community. Website improvement is one of the stages in improving the quality of education and can also be used as a marketing and branding tool for schools. Therefore, it is necessary to design an interface design using the Goals Directed Design (GDD) method, so that users can feel comfortable when using the website. In this (GDD) there are 6 stages, the first is research conducting interviews, observations and initial testing of the website using usability testing, then modeling doing the preparation of user personas and user journeys, then requirements for designing scenario contexts and compiling website information needs, then framework and refinement wireframe design and design prototypes are carried out, the last one is support for testing usability testing on the prototype design and comparing it with the results of the initial testing at the research stage. The results of the initial test obtained an average value of 2.59 on the Likert scale which can be said to be less good. The results of testing the prototype design obtained an average value of 3.14 on the Likert scale which can be said to be good so that it can be used as a recommendation for improvement on the SMA Muhammadiyah 9 Surabaya website.